2018
DOI: 10.1167/iovs.18-23860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Mucolytic Agents on the Tears and Ocular Surface: A Plausible Animal Model of Mucin-Deficient Dry Eye

Abstract: Topical administration of 10% NAC induced ocular surface damage and tear film instability by prompting MUC16 disruption and release from the ocular surface. This animal model could be used to study dry eye disease, especially the mucin-deficiency subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…NAC is nowadays widely used in clinical work as a mucolytic agent to treat patients with too much sputum ( Li et al, 2018a ). However, it was reported that NAC can promote liver functions in NAFLD patients, and there are a number of clinical trials investigating the effect of NAC in treating metabolic syndromes ( Oliveira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAC is nowadays widely used in clinical work as a mucolytic agent to treat patients with too much sputum ( Li et al, 2018a ). However, it was reported that NAC can promote liver functions in NAFLD patients, and there are a number of clinical trials investigating the effect of NAC in treating metabolic syndromes ( Oliveira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a widely applied antioxidant agent, N-acetyl cysteine (NAC) is usually considered as ROS scavenger in basic experimental investigations ( Rushworth and Megson, 2014 ) and is demonstrated to be effective in treating murine diseases such as ischemia/reperfusion injury ( Wang et al, 2014a ) and lung cancer ( Sayin et al, 2014 ). However, in clinical work, it is usually used as a mucolytic agent ( Li et al, 2018a ) and prototypical antidote administered after an acetaminophen overdose, and little attention has been paid to its antioxidant pharmacological property ( Rushworth and Megson, 2014 ). Recently, several limited clinical trials indicated that NAC may be effective in attenuating hepatic dysfunction and ameliorating NAFLD ( Khoshbaten et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Punctuate epithelial staining was recorded according to the standard National Eye Institute grading system of 0–3 to each of five areas of the cornea: central, superior, inferior, nasal, and temporal (total, 15 points). 12 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recently animal models for MAM deficiency were designed by topical application of 10% NAC in male Sprague-Dawley rats for 5 days, four times a day [53]. NAC treated rats showed significant (p < 0.01 compared to controls) decrease in tear secretion, corneal wettability, BUT of TF, tear MUC5AC concentration, and numbers of conjunctival goblet cell.…”
Section: Mam and Corneal Wettabilitymentioning
confidence: 99%